Mother’s Knowledge, Attitude, Practice toward Safe Water Usage and Incidence of Diarrhea in Children at Baleendah Bandung - Eliza Techa Fattima; Kuswandewi Mutyara; Yudith Setiati Ermaya; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Poor environmental conditions contribute to the high incidence of diarrhea, most of those caused by unsecure water and poor health knowledge. This study was conducted to evaluate the mother’s knowledge, attitude, and practice toward safe water usage in Baleendah, Bandung.Methods: A cross sectional descriptive study was conducted in Baleendah during September−October 2012, participated by 210 mothers with 12−59 months children, and using rapid survey method. This study used a questionnaire to measure the three domains, which consists of 8 questions of knowledge, 10 questions of attitudes, 16 questions of practice, and 7 questions of diarrhea. The collected data were analyzed and presented in table.Results: As much as 168 (80%) of mothers were in moderate knowledge status, 126 (60%) of mothers were in moderate attitude status. Practically, 127 (54.7%) of mothers used water from borehole/tube well. Most of the mothers (54.6%) use drinking water from refillable water store.Conclusions: Most mothers who participated have varied moderate knowledge and attitude status, and practice toward safe water usage. DOI: 10.15850/amj.v2n3.503